"My gut feeling is…": Identifying healthcare professionals communication about pain in rheumatology: Presenter(s): Sarah Peters, University of Manchester, United Kingdom. (April 2023) - Lee, Rebecca Rachael; McDonagh, Janet; Rapley, Tim; Farre, Albert; Connelly, Mark; Palermo, Tonya; Toupin-April, Karine; Cordingley, Lis
Abstract : Background: Multi-disciplinary team meetings (MDT's) in paediatric rheumatology regularly meet to discuss children/young people with complex conditions, in which chronic pain may feature. Little is known about healthcare professional to healthcare professional communication and how this may influence the care of children/young people with chronic pain. The objective of the current study was to explore this knowledge gap. Methods: This study was a non-participant ethnographic observation of virtual and face-to-face MDT meetings. Three paediatric rheumatology centres participated. A structured observation checklist was used to capture field notes which were analysed using an inductive thematic approach. Findings: Ten meetings from each team (n=30) were analysed. Analysis was organised into three core inter-related elements of communication: Describing the child/young person with pain: Personality characteristics (e.g. "He is mature" or "sensitive") were frequently used in child/young person introductions. These were always accompanied by a description of parents' personality traits (e.g. "Mum can shout"). Interpreting pain: Familiarity with the child/young person and parents was important (e.g., "I haven't got a handle on them"). Interpretations were also influenced by "gut feelings" or "vibes something else was going on". Managing the child/young person with pain: Healthcare professionals discussed the need for acceptance of pain (e.g., "She wasn't buying into that explanation", "He needs to get used to it"). Setting boundaries for accessing the team also featured in discussions (e.g., "I had to set expectations for mum because it was getting too much"). Discussion: Findings: suggest that healthcare professionals in paediatric rheumatology describe, interpret and manage the child/young person presenting with pain alongside the broader psychosocial (less frequently the biological) context. These Findings: will inform the Methods: and content of a new behaviour change intervention to improve pain communication amongst the paediatric rheumatology team of healthcare professionals in the UK.